2016
DOI: 10.1177/1747016116677250
|View full text |Cite
|
Sign up to set email alerts
|

A case study of researchers’ knowledge and opinions about the ethical review process for research in Botswana

Abstract: Most countries, including Botswana, have established Institutional Review Boards (IRBs) to provide oversight of research involving human beings. Although much has been published on the structure and function of IRBs around the world, there is less literature that empirically describes the perspectives of stakeholders in low-and middle-income country (LMIC) settings regarding IRB processes. In this study, we employed primarily quantitative methods to examine the perceptions of researchers at the University of B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 17 publications
1
3
0
Order By: Relevance
“…Whilst online research ethics courses could be utilized in the short term, the findings from this research also echo the sentiments expressed by previous research that higher academic institutions in low resourced countries must institutionalize research ethics training through the mounting of undergraduate as well as graduate courses (Hyder et al, 2013;Ralefala et al, 2016). In the case of UB, there is a crop of faculty members who have been trained in research ethics (Kass & Hyder, 2015;Ndebele et al, 2014;Oukem-Boyer & Bukusi, 2015).…”
Section: Discussionsupporting
confidence: 76%
See 2 more Smart Citations
“…Whilst online research ethics courses could be utilized in the short term, the findings from this research also echo the sentiments expressed by previous research that higher academic institutions in low resourced countries must institutionalize research ethics training through the mounting of undergraduate as well as graduate courses (Hyder et al, 2013;Ralefala et al, 2016). In the case of UB, there is a crop of faculty members who have been trained in research ethics (Kass & Hyder, 2015;Ndebele et al, 2014;Oukem-Boyer & Bukusi, 2015).…”
Section: Discussionsupporting
confidence: 76%
“…Consistent with this progress, institutions of higher learning in sub-Saharan region seem to be requiring increased training capacity for researchers (Ajuwon & Kass, 2008;Ateudjieu et al, 2010;Coetzee, Hoffmann, & de Roubaix, 2015;Hyder et al, 2013;Millum et al, 2013). Recent studies conducted in Botswana, however, show that limited research ethics training is available for UB academic staff, Institutional Review Board (IRB) members and students (Barchi, Kasimatis-Singleton, Kasule, Khulumani, & Merz, 2013;Barchi, Matlagela, Jones, Kebaabetswe, & Merz, 2015;Hyder et al, 2013;Ndebele et al, 2014;Ralefala, Ali, Kass, & Hyder, 2016). Training that has taken place has been in the form of short workshops and seminars for academic staff and IRB members (Barchi et al, 2013(Barchi et al, , 2015Ralefala et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…As is the case at Alfaisal University, their case study was an initial effort to document researchers’ ethics outreach and education in a context where both research and research oversight are relatively new. Findings revealed that researchers indeed recognized the critical need for research ethics training and that ethics review processes can help researchers better understand and value research ethics [17].…”
Section: Discussionmentioning
confidence: 99%